1988
DOI: 10.1002/j.1537-2197.1988.tb13501.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition Between Schizachyrium Scoparium and Prosopis Glandulosa

Abstract: A competition experiment was carried out in a greenhouse with Schizachyrium scoparium (Michx.) Nash (little bluestem) and seedlings of Prosopis glandulosa Torr. (honey mesquite). The effect of S. scoparium density on the growth of P. glandulosa and the effect of a single P. glandulosa seedling on the growth of various densities of S. scoparium were examined. When P. glandulosa was grown with S. scoparium, there was a significant decrease in P. glandulosa above‐, belowground, and total dry weight at all S. scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Unfortunately, once established, these alien species continue to spread even after disturbance has ceased (Mack 1981, D'Antonio and Vitousek 1992. This profusion of exotic grasses is a potential threat to the indigenous flora, since they can successfully compete with both herbaceous and woody native plants (Schuhz and others 1955;Van Auken and Bush 1988, Cohn and others 1989, Billings 1990 especially in areas of current or past human disturbance (Mack 1986). Specifically, they compete well for limiting resources such as nitrogen Whitford 1987a, Elliott andWhite 1989), water (Schultz and others 1955, Da Silva and Bartolome 1984, Gutierrez and Whitford 1987b, Melgoza and others 1990, and light (Bush and Van Auken 1987, Thompson and Harper 1988, Van Auken and Bush 1990.…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, once established, these alien species continue to spread even after disturbance has ceased (Mack 1981, D'Antonio and Vitousek 1992. This profusion of exotic grasses is a potential threat to the indigenous flora, since they can successfully compete with both herbaceous and woody native plants (Schuhz and others 1955;Van Auken and Bush 1988, Cohn and others 1989, Billings 1990 especially in areas of current or past human disturbance (Mack 1986). Specifically, they compete well for limiting resources such as nitrogen Whitford 1987a, Elliott andWhite 1989), water (Schultz and others 1955, Da Silva and Bartolome 1984, Gutierrez and Whitford 1987b, Melgoza and others 1990, and light (Bush and Van Auken 1987, Thompson and Harper 1988, Van Auken and Bush 1990.…”
Section: Discussionmentioning
confidence: 96%
“…During the period of growth associated with establishment, competition for resources (water, nutrients, light and space) may intensify as dry weight develops. In general, seedlings of woody species rarely compete well with grasses (Van Auken & Bush 1988; Bush & Van Auken 1990); however, most studies have examined legumes or other relatively heavy‐seeded woody species.…”
Section: Discussionmentioning
confidence: 99%
“…In general, seedlings of woody species rarely compete well with grasses (Van Auken & Bush 1988;Bush & Van Auken 1990); however, most studies have examined legumes or other relatively heavyseeded woody species. Time of emergence also plays a major role in seedling mortality and growth in seedling populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of grass-shrub interaction may depend on the species' life history stage and traits (Vilà & Sardans 1999) as well as on environmental conditions (Callaway 1997;Holmgren et al 1997). Studies conducted in several communities such as tropical savannas (Knoop & Walker 1985), seasonally dry woodlands (D'Antonio et al 1998), temperate grasslands (Romo & Eddleman 1987;Van Auken & Bush 1988) and Mediterranean shrublands (Schultz et al 1955;Litav et al 1963;Griffin 1971;Da Silva & Bartolome 1984) have found that woody seedling establishment, survival and growth can be limited by grasses. Grasses may outcompete juvenile woody plants by shading (Van Auken & Bush 1988) and by reducing water availability (Litav et al 1963;Knoop & Walker 1985).…”
Section: Introductionmentioning
confidence: 99%